UM ESTUDO SOBRE A IMPORTÂNCIA DO USO DAS FERRAMENTAS DE CONTROLE GERENCIAL NAS MICRO, PEQUENAS E MÉDIAS EMPRESAS INDUSTRIAIS NO MUNICÍPIO DE SÃO CAETANO DO SUL - Lima, Amadeu Nascimento (2007)
The objective of this study was to evidence the use of the tools of management control that assist in the process of decision-taking in micros, Small and Medium Scale Enterprises, in the City of SCSul. One understands that in the present days these instruments must be aligned with the reality of these organizations and the information extracted for these must be the basis for decision-taking. The applied methodological procedure was chose by convenience, using the method deductive reasoning, through application of a questionnaire in 296 companies, for which 18,6% promised to respond the questionnaire. The companies were been classified in accordance with the annual Income established by the Federal Rules. Upon analysis of the results, we observed that about 41% of these organizations were more than 20 years in the market, which demonstrates a better consolidation in the market. It was also detected, that these entrepreneur-managers possess a strong educational background: 22.22%, graduated and 31.27% postgraduates, such that this represents a competitive edge in the act of business management. As our premise was to investigate how the MSME in the city of SCSul are using the tools of managerial control in its process of management for decision taking, based on our analysis, we conclude that decision taking process in these companies is based on the control tools and that they possess a good control of its businesses, contrary to our expectations.